Efektivitas Model Pembelajaran Missouri Mathematics Project (MMP) Terhadap Kemampuan literasi Matematika Siswa Ditinjau dari Self-Efficacy - Setyowati, Elis; Nurcahyo, Adi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Indonesia is a country with low mathematical literacy skills. Improving the learning model is an action that can be taken to improve students' mathematical literacy skills. The Missouri Mathematics Project (MMP) learning approach is a learning approach that is considered effective in improving mathematical literacy skills. In addition to this, self-efficacy is another factor that can affect students' mathematical literacy skills. The purpose of this study was to determine the effectiveness of the Missouri Mathematics Project (MMP) learning model on students' mathematical literacy in terms of self-efficacy. This study used a quantitative research approach with a quasi-experimental method. The research instruments used essay tests and questionnaires. Hypothesis testing uses the Two-Way Anova test of Unequal Cells. The results concluded that there was an effect of Missouri Mathematics Project (MMP) learning model and self-efficacy on students' mathematical literacy. The interaction of different learning models and self-efficacy has no effect on students' mathematical literacy skills. The results obtained Fcount = 0.106 < Ftable = 4.001 which means H0 is accepted. This means that both conventional learning models and Missouri Mathematics Project (MMP) learning models students with high self-efficacy categories have superior mathematical literacy skills compared to students with moderate or low self-efficacy categories. Based on the research results, it can be concluded that there is an effect of Missouri Mathematics Project (MMP) learning model and self-efficacy on students' mathematical literacy.